Ecological perspective to sustainably manage the secondary forest in the lowland of Doberai Peninsula, Indonesia - JONNI MARWA; ANTONI UNGIRWALU; CHRISTIAN SOLEMAN IMBURI; DONY ARISTONE DJITMAU; AGUSTINUS MURDJOKO; NITHANEL MIKAEL HENDRIK BENU (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Marwa J, Ungirwalu A, Imburi CS, Djitmau DA, Murdjoko A, Benu NMH. 2024. Ecological perspective to sustainably manage the secondary forest in the lowland of Doberai Peninsula, Indonesia. Biodiversitas 25: 2720-2732. This research aims to examine the composition of flora and fauna in secondary forests, with the aim of using the results to provide input for sustainable forest management. Suggestions for proper ecological management have been put forward, as they are crucial for preserving ecosystem functions and protecting species. We revealed that the identified area was a secondary forest with a composition of 225 species and 83 families of vegetation. The distribution was fairly uniform, encompassing 6 life forms: ferns, herbs, lianas, palms, shrubs, and trees. For fauna, the result indicated the presence of 10 species of mammalia, 37 species of aves, 6 species of reptiles, and 4 species of insects. The secondary forest still supports a high species richness of vegetation and fauna. These findings suggest that the secondary forest is undergoing a successional process in which various vegetation, particularly lianas and herbs, compete to gain more sunlight due to increased canopy openness. Forest management must optimize multi-factors, as in this research, and we suggest considering development and conservation, utilization of buffer zones, monitoring vegetation and animal breeding, and reforestation. The balance between development and conservation is critical, offering opportunities for sustainable practices and community involvement.